Thank you for your servitude : Donald Trump's Washington and the price of submission - Leibovich, Mark (Penguin Press, 2022)
"From the author of the #1 New York Times bestseller This Town, the eyewitness account of how the GOP collaborated with Donald Trump to transform Washington's "swamp" into a gold-plated hot tub--and a onetime party of rugged individualists into a sycophantic personality cult"--